Embryonic stem cells as a source of pulmonary epithelium in vitro and in vivo. - Rippon,HJ; Lane,S; Qin,M; Ismail,N-S; Wilson,MR; Takata,M; Bishop,AE (Proc Am Thorac Soc, 2008)
Embryonic stem cells (ESCs) derived from the preimplantation blastocyst are pluripotent and capable of indefinite expansion in vitro. As such, they present a cell source to derive a potentially inexhaustible supply of pulmonary cells and tissue. ESC-derived pulmonary epithelium could be used for in vitro cell or tissue models or, in the future, implanted into the damaged or diseased lung to effect repair. Efforts to date have largely focused on obtaining distal lung epithelial phenotypes from ESCs, notably alveolar epithelium. Several disparate methods have been developed to enhance differentiation of ESCs into pulmonary epithelial lineages; these are broadly based on recapitulating developmental signaling events, mimicking the physical environment, or forcibly reprogramming the ESC nucleus. Early findings of our preclinical experiments implanting differentiated ESCs into the injured lung are also described here. Future efforts will focus on maximizing ESC differentiation efficiency and yield of the target phenotype, as well as characterizing the function of derived cells in vivo and in vitro.